2017
DOI: 10.1177/0956462417689984
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Chlamydia trachomatis and Neisseria gonorrhoeae in an urban public hospital pregnancy termination clinic

Abstract: This study is a follow-up observational study to assess the prevalence of chlamydia (CT) and gonorrhea (GC) among women who undergo a first-trimester surgical termination in a large public, urban hospital-based termination clinic, and to compare the rates to previously published data. We conducted a retrospective chart review on 4197 patients who underwent CT and GC testing before an elective, first-trimester surgical termination between 1 June 2014 and 31 May 2015. The prevalence rates were calculated and com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…A possible justification for these discrepancies may be attributable to geographic and www.nature.com/scientificreports/ climatic variations in different regions of world. Some of the studies documented a very low prevalence of NG in cases of European population 36 while other studies reported a very high prevalence in American population 37 .…”
Section: Discussionmentioning
confidence: 99%
“…A possible justification for these discrepancies may be attributable to geographic and www.nature.com/scientificreports/ climatic variations in different regions of world. Some of the studies documented a very low prevalence of NG in cases of European population 36 while other studies reported a very high prevalence in American population 37 .…”
Section: Discussionmentioning
confidence: 99%